Unexpected disturbance program in rehabilitation of high performance athletes. - Teichmann, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Athletes recovering from anterior cruciate ligament (ACL) injury reached 75-85% of their pre injury level of performance (Haas et al., 2004). Exercises in proprioception training with voluntary corrective movements are widely accepted in post-surgical rehabilitation for ACL reconstruction of athletes. The UDP promotes exercises in response to so-called involuntary short to mid latency disturbances (Taube et al., 2006). A pre - post study design was used to investigate the effectiveness of UDP in the last 6 weeks of rehabilitation of 15 Malaysian national athletes .Tests included 20 m sprint, 1 RM single leg press, standing long jump, sway test and a psychological questionnaire. The rehabilitation consisted of two parts, general training and specific training. A total of 7 sessions per week of 90 minutes with 3 sessions allocated for 5-6 UDP exercises. Conditioning tests were measured with timing system (Brower), measure tape and observation on the outdoor track or in-house gym. Sway was measured as the centre of pressure movement in AP and ML directions, at 100 Hz for a period of 10-15 seconds, on a tri-axial force plate. Sway conditions were semi-randomized in a 3x3x3 design with varying intrinsic, extrinsic conditions and each trial was repeated three times. The non-injured leg served as a control for the injured leg. Two-tailed paired t-tests were used for limited a-priori comparisons to examine differences. Significance level was set at p<0.05. Significant improvements in average time by 3.6% (ES=0.42), strength by 21.6% (ES=1.49), distance jumped by 5.2% (ES=0.36) and ML sway (ES=0.96) were noted. Additionally athletes reported improved perceived confidence in their abilities. All athletes improved in each conditioning tests except for the long jump of two athletes. The ML sway decreased with 9 out of the 15 athletes for the injured limb. Group mean sway showed an overall increase for both the injured and non-injured limb. However, the injured limb increased significantly less in ML sway than the non-injured limb. The increase in sway due to the UDP was unexpected but may be due to athletes` increased ability to correct imbalances with active torque. The prevention training with UDP resulted in improved conditioning and seems to decrease ML sway. Continued research is needed to further confirm these observations.